Advances and Challenges in Understanding Cerebral Toxoplasmosis - Schlüter, Dirk; Barragan, Antonio (Frontiers in Immunology, 2019)
Toxoplasma gondii is a widespread parasitic pathogen that infects over one third of the global human population. The parasite invades and chronically persists in the central nervous system (CNS) of the infected host. Parasite spread and persistence is intimately linked to an ensuing immune response, which does not only limit parasite-induced damage but also may facilitate dissemination and induce parasite-associated immunopathology. Here, we discuss various aspects of toxoplasmosis where knowledge is scarce or controversial and, the recent advances in the understanding of the delicate interplay of T. gondii with the immune system in experimental and clinical settings. This includes mechanisms for parasite passage from the circulation into the brain parenchyma across the blood-brain barrier during primary acute infection. Later, as chronic latent infection sets in with control of the parasite in the brain parenchyma, the roles of the inflammatory response and of immune cell responses in this phase of the disease are discussed. Additionally, the function of brain resident cell populations is delineated, i.e. how neurons, astrocytes and microglia serve both as target cells for the parasite but also actively contribute to the immune response. As the infection can reactivate in the CNS of immune-compromised individuals, we bring up the immunopathogenesis of reactivated toxoplasmosis, including the special case of congenital CNS manifestations. The relevance, advantages and limitations of rodent infection models for the understanding of human cerebral toxoplasmosis are discussed. Finally, this review pinpoints questions that may represent challenges to experimental and clinical science with respect to improved diagnostics, pharmacological treatments and immunotherapies.